What makes randomized controlled trials so successful—for now? Or, on the consonances, compromises, and contradictions of a global interstitial field - Malte Neuwinger (Theory and Society, 2024)
Abstract Randomized controlled trials (RCTs) are a major success story, promising to improve science and policy. Despite some controversy, RCTs have spread toward Northern and Southern countries since the early 2000s. How so? Synthesizing previous research on this question, this article argues that favorable institutional conditions turned RCTs into “hinges” between the fields of science, politics, and business. Shifts toward behavioral economics, New Public Management, and evidence-based philanthropic giving led to a cross-fertilization among efforts in rich and poor countries, involving states, international organizations, NGOs, researchers, and philanthropic foundations. This confluence of favorable institutional conditions and savvy social actors established a “global interstitial field” inside which support for RCTs has developed an unprecedented scope, influence, operational capacity, and professional payoff. However, the article further argues that the hinges holding together this global interstitial field are “squeaky” at best. Because actors inherit the illusio of their respective fields of origin—their central incentives and stakes—the interstitial field produces constant goal conflicts. Cooperation between academics and practitioners turns out to be plagued by tensions and contradictions. Based on this analysis, the article concludes that the global field of RCT support will probably differentiate into its constituent parts. As a result, RCTs may lose the special status they have gained among social science and policy evaluation methods, turning into one good technique among others.
Keywords: 330; Field theory; Global fields; Interstitial fields; Illusio; Policy evaluation; Randomized controlled trials